The European Commission's CC(C)TB re-launch - Katharina Nicolay; Christoph Spengel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
With its Action Plan for a Fairer and Efficient Corporate Tax System (COM (2015) 302) published on 17 June 2015, the European Commission relaunched the idea of a Common Consolidated Corporate Tax Base (European Commission (2015a)). The respective proposals for a Council Directive have recently been published on 25 October 2016 (COM (2016) 683 and 685). The CCCTB promises a harmonized set of rules to determine the tax base, the consolidation of taxable profits at the EU level and formula-based apportionment. The CCCTB does not harmonize corporate income tax rates, which remain within the purview of the Member States.
Keywords: 330